2022
DOI: 10.1155/2022/1318295
|View full text |Cite
|
Sign up to set email alerts
|

Admission Outcome and Antimicrobial Resistance Pattern of Bacterial Isolates among Neonates with Suspected Sepsis in Neonatal Intensive Care Unit at Dessie Comprehensive Specialized Hospital, Dessie, Northeastern Ethiopia

Abstract: Background. Neonatal sepsis is a major cause of morbidity and mortality globally. The aim of this study was to assess admission outcome and antimicrobial susceptibility pattern of bacterial isolates among neonates with suspected sepsis at the Dessie Comprehensive specialized Hospital (DCSH), Northeastern Ethiopia. Method. Cross-sectional study was conducted from August 2017 to March 2018. Two hundred forty-six neonates were recruited, and each patient’s blood specimen was collected aseptically using bottle con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
3
1
2
Order By: Relevance
“…A study conducted in Egypt reported a prevalence of 82% 30 and in India it ranges from 65 to 75% 31 , which is higher than the finding of the current study. Conversely, the current study’s results were higher than studies conducted in United States 9.5% 32 , South Asia 8% 25 , India (5.1%) 33 , and Australia 20% 26 . These differences might be due to variations in the study design, inclusion criteria, and sampling methods.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Egypt reported a prevalence of 82% 30 and in India it ranges from 65 to 75% 31 , which is higher than the finding of the current study. Conversely, the current study’s results were higher than studies conducted in United States 9.5% 32 , South Asia 8% 25 , India (5.1%) 33 , and Australia 20% 26 . These differences might be due to variations in the study design, inclusion criteria, and sampling methods.…”
Section: Discussioncontrasting
confidence: 99%
“…Women who practice ineffective breastfeeding were more likely to develop breast problems than those who practice effective breastfeeding techniques. This finding is supported by a study conducted in Brazil 26 . Poor positioning, attachment, weak or uncoordinated suckling, and incorrect handling of the infant at the mother's breast can lead to nipple trauma and contribute to the development of breast problems.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, the results were as shown that Acinetobacter baumannii is highly resistant, and these results were the same as with [19]; These results were comparable with results of studies conducted by [29] in North eastern Ethiopia.…”
Section: Antibiotic Susceptibility Test Of Acinetobacter Baumanniisupporting
confidence: 91%
“…This can be better explained by the fact that neonates have low neutrophil storage pools which increases the occurrence of reduced number of neutrophils with serious infection (72). In this study, the death rate due to sepsis was 7% which was much smaller than study which reported a 20.9% death rate ( 73), but higher than a study by Fenta et al and Tewabe et al that reported a 4.0% death rate (74,75).…”
Section: Discussioncontrasting
confidence: 52%